Enhancing Students' Pronunciation with the Implementation of the Jazz Chant Method - Yuanita, Rina (INTERACTION: Jurnal Pendidikan Bahasa, 2022)
The pre-experimental study conducted at SMPN 17 Kabupaten Sorong aimed to investigate the effectiveness of implementing the Jazz Chant method to enhance seventh-grade students' pronunciation skills. The research involved a sample of 22 students and utilized a pretest-posttest design to evaluate the impact of the intervention. The initial pretest results revealed a mean score of 63.87, indicating the baseline level of students' pronunciation proficiency before the intervention. Following the implementation of the Jazz Chant method, significant improvements were observed in students' pronunciation abilities. The posttest results showed a substantial increase in the mean score to 80.51, reflecting a notable enhancement in students' pronunciation accuracy and fluency. This improvement suggests that the rhythmic and melodic elements of Jazz Chants effectively contribute to enhancing students' phonological awareness and articulation skills. The findings of the study align with previous research highlighting the benefits of incorporating musical and repetitive techniques, such as Jazz Chants, in language learning to improve pronunciation. The results demonstrate the positive impact of the Jazz Chant method on enhancing students' pronunciation skills, as evidenced by the significant increase in mean scores from the pretest to the posttest. Overall, the study underscores the efficacy of the Jazz Chant method in enhancing seventh-grade students' pronunciation proficiency. By integrating innovative and engaging teaching strategies, educators can create a conducive learning environment that supports students in developing accurate and fluent pronunciation. The results of this research provide valuable insights into the potential of utilizing creative techniques like Jazz Chants to enhance students' language learning outcomes effectively.